2012
DOI: 10.1111/j.1365-4632.2011.05205.x
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and the skin

Abstract: Cigarette smoking has been associated with significant morbidity affecting all systems of the body, including the integumentary system. We review the many dermatologic hazards of tobacco use. It is important to distinguish between the effects of tobacco smoke from effects of pure nicotine on the skin. All skin cells express several subtypes of the nicotinic class of acetylcholine receptors, including the a7 receptor. Many chronic dermatoses are affected by smoking either negatively or positively. Elucidation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
122
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(135 citation statements)
references
References 120 publications
(122 reference statements)
6
122
0
7
Order By: Relevance
“…Smoking is well known to be associated with numerous cardiovascular and respiratory diseases as well as different malignancies. In addition, smoking has been associated with skin changes, such as premature aging, wrinkling, loss of elasticity and abnormal wound healing [2,3,4]. The risk of cutaneous squamous cell carcinoma (SCC) is increased among smokers [2,5], and the risk of recurrence of SCC is also increased in smokers and ex-smokers [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Smoking is well known to be associated with numerous cardiovascular and respiratory diseases as well as different malignancies. In addition, smoking has been associated with skin changes, such as premature aging, wrinkling, loss of elasticity and abnormal wound healing [2,3,4]. The risk of cutaneous squamous cell carcinoma (SCC) is increased among smokers [2,5], and the risk of recurrence of SCC is also increased in smokers and ex-smokers [6].…”
Section: Introductionmentioning
confidence: 99%
“…The risk of cutaneous squamous cell carcinoma (SCC) is increased among smokers [2,5], and the risk of recurrence of SCC is also increased in smokers and ex-smokers [6]. The prevalence of basal cell carcinoma (BCC) of the skin among smokers has been investigated and although the issue remains somewhat unclear [2], there is some proof that smokers are more likely to have higher-risk type of BCC, such as morpheaform BCC, than non-smokers [7]. …”
Section: Introductionmentioning
confidence: 99%
“…Smoking not only induces inflammation, but also delays wound healing, partly because it decreases cutaneous blood flow and causes chronic damage to the microcirculation, thus compromising tissue oxygenation. In addition, fibroblast migration into lesional skin is inhibited (13,14). Smoking has been suspected to be a risk factor for skin diseases such as lupus erythematosus (15,16), palmoplantar pustulosis (17,18), psoriasis (19,20), and hidradentis suppurativa (21).…”
mentioning
confidence: 99%
“…The HHV8 has rarely been present in other vascular neoplasms, such as angiosarcoma, reactive angioendotheliomatosis, and in the lesions of patients, who harbor HHV8, so clinicopathologic correlation is mandatory (7). It has been reported that smoking may interfere in classic presentation of KS, similar to the current patient (8). Nephrectomy in this case was due to abscess formation after complicated renal stone 30 years ago, thus it seems it has not had any association with development of the lesions.…”
Section: Discussionmentioning
confidence: 64%